Unpacking the water-energy-environment-food nexus: working across systems - Sood, Aditya; Nicol, Alan; Arulingam, Indika (International Water Management Institute, 2019)
The increasing demand for water, energy and food, and the interdependence of these systems could lead to potential human conflict in the future. This was seen in the food crisis of 2008, which stirred a renewed interest in taking a "systems" approach to managing resources. The initial flurry of activities led to many nexus frameworks, but there remains a gap between theory and its implementation. This paper tries to look at various frameworks and unpacks the concept of nexus in order to develop matrices to help quantify and understand the interlinkages between the nexus systems. It suggests multi-level and multi-system indices to measure the health of nexus systems and to identify the weak links. It is hoped that such frameworks can be used at country level, and eventually be used to measure and rank countries on the health of their systems. The paper suggests a questionnaire that can be used (after modifying for local conditions) to collect country-level institutional and political-economy data (which is difficult to get from online resources) to be used in the framework.